Incorporating Religious Moderation Values Through English Language Teaching (ELT) Instructional Materials to Prevent Religious Intolerance - M. Ali Ghufron (2022)
In recent years, Indonesian educational institutions and authorities have been concerned about religious intolerance and cultural diversity. According to some reports, Indonesia has recently seen an increase in the number of incidents involving religious intolerance as well as violations. Therefore, Indonesia's national motto,